2013
DOI: 10.1159/000357102
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Transfusion-Transmitted Cytomegalovirus Infections: Which is the Optimal Strategy?

Abstract: Traditionally, leukoreduction and selection of blood products from seronegative donors have been used as alternative strategies to reduce the risk of transfusion-transmitted cytomegalovirus infections (TT-CMV) in atrisk patients. After the introduction of universal leukoreduction for red blood cell and platelet concentrates in Germany, a controversy evolved as to whether the additional selection of blood products from seronegative donors would reduce or even increase the risk of TT-CMV. This review summarizes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 29 publications
0
28
0
3
Order By: Relevance
“…In many developed countries, it is not mandatory to screen donated blood for CMV in blood banks (8,11). That is why Kothari et al suggested that the estimation of the seroprevalence among voluntary blood donors may be of help to decide whether screening for CMV would eliminate transmission of infection to high-risk groups (29).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In many developed countries, it is not mandatory to screen donated blood for CMV in blood banks (8,11). That is why Kothari et al suggested that the estimation of the seroprevalence among voluntary blood donors may be of help to decide whether screening for CMV would eliminate transmission of infection to high-risk groups (29).…”
Section: Discussionmentioning
confidence: 99%
“…Vulnerable groups to serious illness caused by this virus are immunocompromised hosts, neonates and pregnant women (5,6). Exclusion of seropositive blood units and leucodepletion are the two main strategies to minimize CMV transmission to high risk recipients (11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…42,46 This potential risk has led to proposals that LR-only blood products be collected from donors who have been seropositive for at least 1 year or that the donors also be screened for CMV by PCR. 34,45,47 However, it remains to be determined whether the latter would be a cost-effective way to further decrease the risk of TT-CMV infection. For example, a recent study detected CMV DNA in the plasma of only 0.03% of blood donors.…”
Section: Harmon and Coolingmentioning
confidence: 99%
“…Beim derzeitigen Wissenstand ist keine Präferenz für eine Methode sicher belegbar [135]. Nach Verfügbarkeit des WHO-Standards für HCMV-DNA, kommerzieller Assays und Ringversuche ist eine höhere Standardisierbarkeit und Vergleichbarkeit der NAT-Methoden gegeben [136][137][138].…”
Section: Bekanntmachungen -Amtliche Mitteilungenunclassified